2009
DOI: 10.2298/jsc0904389k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) complexes with R2edda derived ligands, Part I: Reaction of diisopropyl (S,S)-2,2'-(1,2-ethanediyldiimino)- dipropanoate with K2[PdCl4]

Abstract: The reaction of K 2 [PdCl 4 ] with (S,S)-(i-Pr) 2 eddip diester (diisopropyl (S,S)-2,2'-(1,2-ethanediyldiimino)dipropanoate) resulted in {PdCl 2 [(S,S)-(i--Pr) 2 eddip-κ 2 N,N']} (1) and {PdCl[(S,S)-(i-Pr)eddip-κ 2 N,N',κO]}(2) with one hydrolyzed ester group. The compounds were characterized by spectroscopic methods and it was proved that the reaction is diastereoselective ( 1 H-and 13 C-NMR) in the case of 2 (one diastereoisomer of four possible). The structure of 2 was determined by X-ray diffraction analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
4
9
0
1
Order By: Relevance
“…IR spectra are similar to those of the previously reported compounds [40,41]. Absorption bands for secondary amino groups were found for 1e4 at 3088, 3143, 3133, 3139 cm À1 , respectively, indicating coordination via nitrogen atoms (for ligand precursors only bands for secondary ammonium groups can be observed; L1$2HCleL4$2HCl: n(R 2 NH 2 þ ) at 3457, 3453, 3455, 3452 cm À1 ).…”
Section: Spectroscopic Measurementssupporting
confidence: 84%
See 1 more Smart Citation
“…IR spectra are similar to those of the previously reported compounds [40,41]. Absorption bands for secondary amino groups were found for 1e4 at 3088, 3143, 3133, 3139 cm À1 , respectively, indicating coordination via nitrogen atoms (for ligand precursors only bands for secondary ammonium groups can be observed; L1$2HCleL4$2HCl: n(R 2 NH 2 þ ) at 3457, 3453, 3455, 3452 cm À1 ).…”
Section: Spectroscopic Measurementssupporting
confidence: 84%
“…1. A, B) [7,40] and isobutyl ester of (S,S)-ethylenediamine-N,N 0 -di-2-(4-methyl)-pentanoic acid dihydrochloride, [(S,S)-H 2 iBu 2 eddl]Cl 2 ( Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd-N bond lengths (2.028(7) and 2.043(7) Å ) are comparable with those found in [PdCl{(S,S)-(iPr)eddip}] complex (1.995(5)-2.047(6) Å ) [22] and in Pd(II) complexes with ethylenediamine ligands (2.03-2.09 Å ) [23,24]. On the other hand, the Pd-N bond lengths are shorter than those found in palladium complexes with edta tetraalkyl ester ligands (2.098(4)-2.106(7) Å ) [8,[25][26][27] [28,29].…”
Section: Spectroscopic Propertiessupporting
confidence: 78%
“…It was found that the (R,R)-N,N′ configured isomer with a κ 2 N,N′,κO coordination mode was obtained, and that this is the most stable isomer of four theoretically possible ones. 7 All of the other complexes mentioned here have a κ 2 N,N′ coordination mode of the ligand.…”
Section: Introductionmentioning
confidence: 86%
“…1 were obtained as a mixture of two diasteroisomers, as (R,R) and (R,S) isomers, as verified by 1 H-and 13 C--NMR spectroscopy and supported by DFT calculations. 7,8 However, three diastereoisomers can be formed in theory, (R,R), (S,S) and (R,S) ≡ (S,R), due to the formation of chiral centers on the coordinated nitrogen atoms. In a recent study a palladium(II) complex with a partially hydrolized isopropyl ester of N,N′-1,2-ethanediylbis-L-alanine ( Fig.…”
Section: Introductionmentioning
confidence: 99%